Mermaids never drown : tales to dive for - Córdova, Zoraida; Parker, Natalie C.; Coffindaffer, Rebecca; Winters, Julian; Schreiber, Gretchen; Chhibber, Preeti; Bayron, Kalynn; Little Badger, Darcie, 1987-; Maniscalco, Kerri; Herrera, Adriana (Romance author); Locke, Katherine; Murphy, Julie, 1985-; et al. (Untold legends ;, 2023)
"The second book in the Untold Legends series, this is an anthology of short stories that feature mermaids"--